Microarray-Based Allergy Diagnosis: Quo Vadis? - Huang, Huey-Jy; Campana, Raffaela; Akinfenwa, Oluwatoyin; Curin, Mirela; Sarzsinszky, Eszter; Karsonova, Antonina; Riabova, Ksenja; Karaulov, Alexander; Niespodziana, Katarzyna; Elisyutina, Olga; Fedenko, Elena; Litovkina, Alla; et al. (Frontiers in Immunology, 2021)
More than 30% of the world population suffers from allergy. Allergic individuals are characterized by the production of immunoglobulin E (IgE) antibodies against innocuous environmental allergens. Upon allergen recognition IgE mediates allergen-specific immediate and late-phase allergic inflammation in different organs. The identification of the disease-causing allergens by demonstrating the presence of allergen-specific IgE is the key to precision medicine in allergy because it allows tailoring different forms of prevention and treatment according to the sensitization profiles of individual allergic patients. More than 30 years ago molecular cloning started to accelerate the identification of the disease-causing allergen molecules and enabled their production as recombinant molecules. Based on recombinant allergen molecules, molecular allergy diagnosis was introduced into clinical practice and allowed dissecting the molecular sensitization profiles of allergic patients. In 2002 it was demonstrated that microarray technology allows assembling large numbers of allergen molecules on chips for the rapid serological testing of IgE sensitizations with small volumes of serum. Since then micro-arrayed allergens have revolutionized research and diagnosis in allergy but several unmet needs remain. Here we show that detection of IgE- and IgG-reactivity to a panel of respiratory allergens micro-arrayed onto silicon elements is more sensitive than glass-based chips. We discuss the advantages of silicon-based allergen microarrays and how this technology will allow addressing hitherto unmet needs in micro-array-based allergy diagnosis. Importantly, it is described how the assembly of silicon micro-array elements may create different micro-array formats for suiting different diagnostic applications such as quick testing of single patients, medium scale testing and fully automated large scale testing.